Impact of endotracheal tube size and cuff pressure on tracheal and laryngeal mucosa of adult horses. (November 2021) - Ferreira, Tatiana H.; Allen, Molly; De Gasperi, Diego; Buhr, Kevin A.; Morello, Samantha L.
Abstract: Objective: To assess the effects of two sizes of silicone endotracheal tubes with internal diameter 26 mm (ETT26 ) and 30 mm (ETT30 ) inflated to minimum occlusive volume on tracheal and laryngeal mucosa of adult horses anesthetized for 2 hours with isoflurane. Study design: Prospective, randomized, blinded, crossover experimental study. Animals: A total of eight healthy adult mares. Methods: Upper airway endoscopy and ultrasound measurements of internal tracheal diameter were performed the day before anesthesia. Horses were anesthetized and orotracheally intubated with ETT26 or ETT30 . Ease of intubation was scored. The cuff was inflated in 10 mL increments to produce a seal. Final volume of air used and intracuff (IC) pressure (measured by pressure transducer) were recorded. At the end of anesthesia, a manometer was used to measure IC pressure and these measurements compared against measurements from the pressure transducer. Laryngeal and tracheal mucosa were assessed via endoscopy and assigned a score 0–3 before anesthesia, and at 2 and 24 hours following extubation. Results: Data are from seven horses because one horse with laryngeal hemiplegia was excluded. Mean tracheal ultrasound measurement was 3.5 ± 0.4 cm. No significant differences were noted between endotracheal tube sizes for intubation score, IC pressures, inflation volumes or tracheal or laryngeal injury scores at any time point. IC pressure measured by manometer was slightly higher than that by transducer (+1.0 ± 2.8 mmHg). Conclusions and clinical relevance: Results identified no clear advantage of one endotracheal tube size over the other in the population of horses studied, when endotracheal intubation is properly applied and IC pressure is carefully monitored. However, given that ETT26 was associated with the highest observed IC pressures and the only observed incidents of tracheal circumferential erythema, the larger ETT30 may be the better choice in most cases where tracheal size is sufficient.